Grammar, numerals, and number words a Wittgensteinian reflection on the grammar of numbers - De Vera, Dennis A. (Social Science Diliman, 2014)
What account of meaning is sufficient for understanding expressions? Using numbers and number-words as familiar forms of expression, I shall try to make an apology of Wittgenstein’s treatment of meaning. My apology is of two parts. The first part attempts to address two questions: Firstly, how do we account for our knowledge of mathematical objects such as those of numbers, numerals, and number-words? Secondly, how do we account for the meaningfulness of their application outside the domain of mathematics?